2022
DOI: 10.31234/osf.io/xf3zb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the trajectory and correlates of social isolation for veterans across a 6-month period during COVID-19

Abstract: Social isolation is a relevant problem for veterans who are at risk for disengaging from others as a function of transition stress from military life to civilian life, and given high rates of exposure to trauma and psychological distress. Few researchers have examined social isolation in veterans over time, particularly during COVID-19 that led to significant barriers and restrictions on social interactions. The purpose of this longitudinal study was to assess veterans’ experience of social isolation and its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, rehabilitation counselors may find peer support specialists (Fortuna et al, 2019(Fortuna et al, , 2021 who have knowledge and expertise on working with Veterans with disabilities given Veterans prefer working with their fellow Veterans. Finally, although these data were not collected during the pandemic, we strongly believe that this study provides us promise that improving positive emotions and sense of accomplishment may help student Veterans to buffer negative impact of COVID-19 on persons with disabilities and college students as reported by research (Ibarra-Mejia et al, 2022;Lee et al, 2021;McGuire et al, 2022;Umucu, 2021b;Umucu & Lee, 2020;Umucu, Lee & Bezyak, 2022;Umucu, Reyes, Urkmez, et al, 2022).…”
Section: Implications For Practice and Researchmentioning
confidence: 78%
“…In addition, rehabilitation counselors may find peer support specialists (Fortuna et al, 2019(Fortuna et al, , 2021 who have knowledge and expertise on working with Veterans with disabilities given Veterans prefer working with their fellow Veterans. Finally, although these data were not collected during the pandemic, we strongly believe that this study provides us promise that improving positive emotions and sense of accomplishment may help student Veterans to buffer negative impact of COVID-19 on persons with disabilities and college students as reported by research (Ibarra-Mejia et al, 2022;Lee et al, 2021;McGuire et al, 2022;Umucu, 2021b;Umucu & Lee, 2020;Umucu, Lee & Bezyak, 2022;Umucu, Reyes, Urkmez, et al, 2022).…”
Section: Implications For Practice and Researchmentioning
confidence: 78%
“…The PHQ-4 was used to measure depression and anxiety. The internal consistency reliability coefficient was found to be .82 (Löwe et al, 2010). Items of the PHQ-4 and of the subscales of the ICP are negatively worded, so negatively worded items were reverse coded.…”
Section: Methodsmentioning
confidence: 94%
“…Social support is an important protective factor for student veterans as they adjust to college life. Research revealed that veterans may experience social isolation (e.g., Grenawalt, Lu et al, 2022;McGuire et al, 2022). Similarly, student veterans may experience interpersonal problems due to difficulties related to their nontraditional student status, health problems, and transition to college life (Barry et al, 2014;.…”
Section: College Adjustment/well-being Health-related Quality Of Life...mentioning
confidence: 99%
“…Meredith et al (2011) had advocated for strengthening policies to clearly define the factors within building resilience and provide guidance on program implementation. We believe positive psychology factors may play an important role in reducing stigma and improve overall quality of life and well-being in veterans, including student veterans with and without disabilities (McGuire et al, 2022; Umucu, Lo, et al, 2022; Umucu, Villegas, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%